Design of a Shielded Room against EMP Signal as per MIL-STD 461 - Pathala, Venkata Sai Charishma; Jayasree, Pappu V. Y. (Engineering, Technology & Applied Science Research, 2023)
Electromagnetic shielding is the best technique to protect equipment from the Electromagnetic Pulse (EMP) signal. This paper explains how effectively the equipment will be protected within a shielded room against EMP signals. The shielded room is designed with different points of entry used to provide electrical connections to the Equipment Under Test (EUT) in a honeycomb structure for ventilation to protect the equipment from the EMP signal. The shielded room with four points of entry and honeycomb structures is designed, analyzed theoretically, and simulated in the CST Studio. The points of entry (PoE) and the honeycomb structure are designed based on MIL-STD-461 E/F/G (by following this standard the maximum frequency of EMP signal is 100MHz). It is observed that by increasing the size of the PoE the shielding effectiveness value decreases by 20dB for perfect electrical conductor (PEC) material of 2mm thickness. It is concluded that the equipment will be more protected when it is placed nearer to the front wall or in the middle of the shielded room. The performance of the shielded room will not be affected with honeycomb structures which will provide 220dB Shielding Effectiveness (SE).